PENGARUH SUPERVISI AKADEMIK` KEPALA SEKOLAH DAN IKLIM ORGANISASI SEKOLAH TERHADAP KINERJAGURU SMA NEGERI - Sidik, Muhammad; Chiar, H.M.; Sukmawati, Sukmawati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract In this study the authors will examine whether School Principal Supervision and Climate School organization affect the performance of teachers (PNS) in SMA Negeri in Sub-Rayon 2 Sambas District. The number of respondents from 10 SMA Negeri in Sub-Ryon 2 was 102 respondents. The research approach used quantitatively with descriptive and parametric analysis techniques. The results showed that Supervision performed by headmaster in Sub-Rayon 2 Sambas District was in good enough category with an average acquisition of 82,27. The results of the hypothesis of supervision of principal (X1) on teacher performance (Y) in obtaining the value of P value of 0.027 ˂ 0.05.It is an  acceptance of Ha (alternative Hypothesis), so it is concluded that there is influence of School Supervision  on teacher Performance. Ther esult of test of second hypothesis Climate of School Organization (X2) to performance (Y) obtained p value 0,007 ˂ 0,05. This shows the acceptance of Ha(Alternative Hypothesis) so it can be concluded that the Climate School organization (X2) affects the performance of teachers (Y).  Keywords: Headmaster Supervision, School Climate Organizations, Teacher Performance.